Security community, ASEAN and its member states: mutually reinforcing or a relationship of convenience? - Mohd Ikbal Mohd Huda; Syed Farizal Aminy Syed Mohamad; Nurliana Kamaruddin (Penerbit Universiti Kebangsaan Malaysia, 2020)
ASEAN, despite its significant achievements and status as the most important international organization in the Southeast Asian region has constantly been met with criticisms, particularly in the role it played towards maintaining security in the region. This article seeks to examine the relationship between ASEAN (as an international organization) and member states; in terms of how they utilize the organization for collective security. It looks first at the evolving concept of security followed by an examination of the theoretical security framework in the context of “states” versus “institution”. The article then looks at the ASEAN Way as a method utilized by its member states in managing their affairs as well as the relationship between ASEAN as an organization and its individual member states in the context of security community building. The article finds that despite its limitation as a regional organization, ASEAN and its member states exists under the condition of mutual interdependence when it comes to forging regional security